Implementation Strategy of 9-Year Compulsory Basic Education Policy In Serang Banten - Lia Amalia; Neti Karnati; Nurhatatti Fuad (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
The article was to find out the strategy in 9-year compulsory basic education policy implementation in Serang. The achievement of compulsory education programs supported the achievement of the vision and mission of national education. All Indonesian citizens have the opportunity to receive basic education. The study focused on planning, development of policy stabilization patterns, socialization, and monitoring. This study used a qualitative descriptive method. The process of collecting data used observation, documents and interviews. Data analysis techniques were data reduction, data presentation, discussion and conclusions. The results show that the process of the nine-year compulsory basic education program has been carried out sequentially in accordance with the activities specified to achieve the program's objectives. Thus, the results of this study recommend that the government in Serang used the appropriate strategy as local tradition and culture. Keywords: Basic 9-Years Compulsory Education, Education Policy, Management Education